Oral proliferative verrucous leukoplakia: A case report with an update - Rakhi Issrani; Namdeo Prabhu; Vaishali Keluskar (Wolters Kluwer Medknow Publications, 2013)
White lesions both physiologic as well as pathologic are relatively frequent in the oral cavity, the most common pathology being oral leukoplakia (OL). There are many variants of OL, one of which is oral proliferative verrucous leukoplakia (OPVL). OPVL is a rare clinico-pathological entity, which is slow growing, long-term progressive lesion, but remains an enigmatic and difficult to define. The etiology of OPVL remains still unclear. Tobacco use does not seem to have a significant influence on the appearance of OPVL. These lesions may occur both in smokers and non-smokers. It is observed more frequently in women and elderly patients over 60 years at the time of diagnosis. The buccal mucosa and tongue are the most frequently involved sites. It develops initially as a white plaque of hyperkeratosis that eventually becomes a multifocal disease with confluent, exophytic and proliferative features. Various published case series have presented OPVL as a disease with aggressive biological behavior due to its high probability of recurrence and a high rate of malignant transformation. Prognosis is poor for this seemingly harmless-appearing white lesion of the oral mucosa. This article describes the clinical aspects and histologic features of an OPVL case that demonstrated the typical behavior pattern in a long-standing, persistent lesion and discusses this relatively rare entity in light of current information.